Menggagas Sistem Pengupahan dan Kesejahteraan Pekerja Outsourcing di Pemerintah dalam Pengadaan Publik - Ajik Sujoko (Administrative Law and Governance Journal, 2018)
AbstractAcceptance of wages and welfare of outsourcing workers in government an interesting thing to be discussed. The first, because wages and welfare in outsourcing are quite relevant issues for labor conditions. Second, through outsourcing, the government is able to accommodate outsourcing workers whose trends increase each year. Third, the government are not in the form of the company but are already used to implementing outsourcing practices. Fourth, the tendency of private participation to improve the performance of the government which is profit oriented. Of the four discussions and cases of outsourcing in some places, the attractive position of outsourcing workers is always in a weak position and an uncertain future, including in government. By reviewing the practice of procurement process of government goods/services, through this article contributes and encourages to government and outsourced employers has the ability and willingness to provide wages and welfare of outsourcing workers. How wages and welfare are enjoyed and accepted by outsourcing workers, through public procurement can be done adequacy of the procurement budget, provider selection process that follows labor regulations and contracting properly with the providerKeywords: Wages, Welfare, Outsourcing Workers, Procurement Of Goods/ServicesAbstrakPenerimaan upah dan kesejaheteraan pekerja outsourcing di pemerintah hal yang menarik untuk didiskusikan. Yang pertama, karena upah dan kesejahteraan dalam outsourcing merupakan masalah yang cukup relevan menggambarkan kondisi tenaga kerja. Kedua, melalui outsourcing pemerintah mampu menampung pekerja outsourcing yang cenderung naik tiap tahun. Ketiga, pemerintah bukan sebuah perusahaan, namun telah biasa menggunakan praktik outsourcing. Keempat, kecenderungan partisipasi swasta untuk meningkatkan kinerja pemerintah yang berorientasi pada keuntungan. Dari empat diskusi dan kasus outsourcing di sebagian tempat, menariknya posisi pekerja outsourcing selalu dalam posisi yang lemah dan masa depan yang tidak pasti, termasuk di pemerintahan. Dengan melihat praktek proses pengadaan barang/jasa pemerintah, melalui artikel ini diharapkan memberikan kontribusi dan dorongan kepada pemerintah dan pengusaha outsourcing memiliki kemampuan dan kemauan untuk menyediakan upah dan kesejahteraan pekerja outsourcing. Bagaimana upah dan kesejahteraan dapat dinikmati dan diterima oleh pekerja outsourcing melalui pengadaan publik, dapat dilakukan dengan menyediakan kecukupan dari anggaran pengadaan, proses pemilihan penyedia yang mengikuti peraturan ketenagakerjaan dan kontrak dengan penyedia secara benar.Kata kunci: Upah, Kesejahteraan, Pekerja Outsourcing, Pengadaan Barang/Jasa